AN EXPERIMENTAL CHAMBER FOR TESTING ABATEMENT EFFECTS OF RADON EXPOSURE WITH DIFFERENT MEASURES. Issue 3 (16th May 2019) - Zhuo, W; Chen, B; He, L; Zhang, W
Abstract: For more effective testing the abatement effects of radon exposure with different counter measures, an air-conditioned laboratory room was reformed as an experimental chamber. Based on the well control and real time monitoring of concentrations of 222 Rn, its attached and unattached progeny and their size distributions, the chamber could provide three modules corresponding to ventilation, source reduction and filtration for abating radon exposure. Preliminary results showed that the chamber was useful for testing the abatement effect of indoor radon exposure.